Sistem Pendukung Keputusan Penentu Beasiswa dengan Simple Additive Weighting - Muhammad Nugraha; Heti Mulyani; Halimil Fathi (Jurnal Informatika Universitas Pamulang, 2021)
Many scholarship applicants are a challenge for the management of educational institutions. Institutions are required to be able to determine the awarding of scholarships with the right target. Currently, the decision to grant scholarships at the Indorama Engineering Polytechnic is still being done manually, and there is no analysis in assessing the eligibility of the scholarship award. Because this requires a decision support system that can help determine alternative decisions in determining scholarship recipients. One of the methods of Decision Support Systems is Simple Additive Weighting (SAW). The concept of SAW method is to find the weighted sum of the ratings for each alternative across all criteria. The criteria used in this study consisted of cost criteria, namely salary/income, as well as benefit criteria, namely: number of dependents, selection value, school average score. In this study, the application was built based on a website using the PHP programming language. The results of this study are in the form of an application that can carry out the process from registering prospective scholarship recipients to calculating the sum of the matrix which has been automatically normalized with the weights for each criterion. The value of the calculation results will be sorted, determine by the rank of the prospective scholarship recipients.